Znamienici profesorowie i absolwenci królewskich katolickich seminariów nauczycielskich w Pilchowicach i Pyskowicach - Koenig, Franciszek (Studia Pastoralne, 2026)
Royal Catholic Teacher Seminars, which first appeared at the beginning of the 19th century as a result of Prussian educational reform, took on an important mission of training future organists. Therefore in many Silesian parishes of the 19th and the first half of the 20th centuries it was a common practice for teachers to be organists at the same time. As it is shown by the experiences of Upper Silesia, teacher seminars were the source of highly qualified church musicians. This resulted from the commitment of very good and skilful music teachers who produced remarkable graduates that later became important figures in Silesian tradition of church music. Among teacher seminars of Upper Silesia that played the most important role in the field of church music particularly noteworthy are the seminars in Pilchowice and Pyskowice. The seminar in Pilchowice existed from 1867 to 1921. Music teachers there were Theophil Halama, Richard Kügele, Wilhelm Osburg, Viktor Kotalla and Franz Werner. The most famous graduates of this seminar in the field of music were Ryszard Gillar, Karol Hoppe and Karl Bauch. The seminar in Pyskowice functioned from 1849 to 1922. Its most prominent music teachers were Józef Nachbar, Paul Gaide, Erdmann Emanuel Wittor, Paul Woehl, Hans Cisner and Vinzenz Laska. Among many graduates of this seminar were Max Borowka, Paul Kraus, Wilhelm Masse, Ernst Gratza, Franz Leischner, Erich Lokay and already mentioned Erdmann Emanuel Wittor.